THE IMPORTANCE OF L1 IN SECOND LANGUAGE ACQUISITION (Modern education and development, 2025)
This article explores the role of a learner's first language (L1) in the process of second language acquisition (SLA). Drawing on key theories such as Krashen's Input Hypothesis, Cummins’ Interdependence Hypothesis, and sociocultural perspectives, the paper highlights both the facilitating and hindering effects of L1 on learning a second language (L2). While L1 can serve as a cognitive and pedagogical tool, helping learners understand and retain new linguistic concepts, excessive reliance on L1 may lead to negative transfer and reduced immersion in the target language. Through a balanced review of research and practical implications, this study underscores the need for thoughtful integration of L1 in L2 classrooms, advocating for strategic use that supports comprehension without limiting exposure to authentic L2 input. The paper concludes with recommendations for educators on how to effectively harness the benefits of L1 while minimizing its potential drawbacks.